Microstructure and mechanical properties of directionally ordered porous Ti3SiC2 prepared using freeze casting. Issue 15 (December 2022) - Du, Wenbo; Yao, Zhengjun; Tao, Xuewei; Zhang, Fan; Shu, Changqing; Long, Man; Wang, Zihe; Zhang, Shasha
Abstract: Directionally ordered porous Ti3 SiC2 embodied in lamellar porous and scaffold structures were prepared using freeze casting. The maximum compression stress was higher than that with a disordered structure, and increased from 22 MPa to 89 MPa as the solid content increased from 15 to 25 vol%. The elastic deformation exhibited an opposite trend. The Young's modulus of the directionally ordered porous Ti3 SiC2 was nearly linear and obeyed the parallel model ( E = 122 – 147 δ ) . The deviation from the theoretical value was due to the difference between the real scaffold structure and that of the theoretical model. Cyclic loading of the porous Ti3 SiC2 at the elastic stage indicated that the energy dissipation (Wd) per loop increased from 0.0009 to 0.0139 MJ/m 3 with a porosity increase. The fracture failure behaviours were mainly splitting and fragmentation. The absorbed-in-fracture energy increase mechanisms during the irreversible deformation of the plastic stage included kink bands, crack extension, and delamination.